External validation of multidimensional prognostic indices (ADO, BODEx and DOSE) in a primary care international cohort (PROEPOC/COPD cohort). Issue 1 (December 2016) - Espantoso-Romero, Maite; Román Rodríguez, Miguel; Duarte-Pérez, Ana; Gonzálvez-Rey, Jaime; Callejas-Cabanillas, Pedro; Lazic, Durdica; Anta-Agudo, Berta; Torán Monserrat, Pere; Magallon-Botaya, Rosa; Gerasimovska Kitanovska, Biljana; Lingner, Heidrun; Assenova, Radost; et al.
Abstract Background Due to the heterogeneous and systemic nature of the chronic obstructive pulmonary disease (COPD), the new guidelines are oriented toward individualized attention. Multidimensional scales could facilitate its proper clinical and prognostic assessment, but not all of them were validated in an international primary care cohort, different from the original ones used for model development. Therefore, our main aim is to assess the prognostic capacity of the ADO, BODEx and DOSE indices in primary care for predicting mortality in COPD patients and to validate the models obtained in subgroups of patients, classified by revised Global Initiative for Chronic Obstructive Lung Disease (2011) and updated Spanish Guideline (2014). Besides, we want to confirm that the prognostic capacity of all indices increases if the number of exacerbations is substituted by the interval between them and to assess the impact on health of the patient's lifestyle, social network and adherence to treatment. Methods Design: External validation of scales, open and prospective cohort study in primary care. Setting: 36 health centres in 6 European high, medium and low income countries. Subjects: 477 patients diagnosed with COPD, captured in clinical visit by their General Practitioner/Nurse. Predictors: Detailed patient history, exacerbations, lung function test and questionnaires at baseline. Outcomes: Exacerbations, all-cause mortality and specific mortality, within 5 years of recruitment. Analysis: Multivariate logistic regression and Cox regression will be used. Possible non-linear effect of the indices will be studied by using Structured Additive Regression models with penalised splines. Subsequently, we will assess different aspects of the regression models: discrimination, calibration and diagnostic precision. Clinical variables modulated in primary care and the interval between exacerbations will be considered and incorporated into the analysis. Discussion The Research Agenda for General Practice/Family Medicine highlights that the evidence on predictive values of prognostic indices in primary care is scarce. A prospective cohort like that ofPROEPOC/COPD provides good opportunities for research into COPD and make communication easier between family practitioners, nursing staff, pneumologists and other professionals, supporting a multi-disciplinary approach to the treatment of these patients. Trial registration ISRCTN52402811 . Date: 15/01/2015. Prospectively registered.